The design and application of a disposable negative pressure device for collecting drainage fluid specimens (一次性医用负压式引流液标本收集装置的设计与应用) - FAN Wenjuan (范文娟); ZHAO Jie (赵洁); YIN Lei (尹磊); FU Xiaohui (傅晓辉) (中西医结合护理)
This paper introduced the design and application of a disposable negative pressure device for collecting drainage fluid specimens. The purpose of this design is to modify the process of collecting drainage fluid specimens, reduce the workload of nurses and avoid the false positive results caused by multiple factors. (本文介绍一种一次性医用负压式引流液标本收集装置的设计与应用方法, 旨在减少留取引流液标本的环节, 节约护士操作时间, 避免留取过程中多环节导致假阳性。)